STUDY OF COST AND TIME ON ACCELERATION OF ASRAMA BUILDING DEVELOPMENT PROJECT PUTRA MADRASAH ALIYAH NEGERI INSAN CENDEKIA PELAIHARI TANAH LAUT DISTRICT - AULIA ISRAMAULANA (Program Studi Teknik Sipil Universitas Narotama, 2020)
Project Construction of the Male Dormitory Building of the State Aliyah Madrasah of the Pelaihari Scholar in Tanah Laut District has experienced delays in the process due to several factors that were not previously taken into account in the planning before the construction project took place. For example, during preparatory work, quarrying work, reinforcing concrete work and other work that has been delayed starting from the beginning of the analysis. The analysis is to make a Work Breakdown Structure (WBS), making a logic analysis of child diagram dependence after the dependency analysis of the master work . PDM is made for master work. The alternative acceleration used is to add workers and increase working hours. The calculation starts with searching for a critical path using the Precedence Diagram Method (PDM) scheduling method and then crashing to get time acceleration and knowing the addition of optimum costs. When the project is completed, the duration of 203 days is at a cost of Rp. 2,614,202,339.23 with a delay of 28 days. by adding as many as seven workers in the critical route obtained 203 days at the cost of Rp.2,626,442,339.23, by increasing the working hours by 4 hours obtained a duration of 203 days at the cost of Rp. 2,643,252,339.23. Then a more efficient acceleration is by adding 7 workers with a difference in cost of Rp. 12,240,000.00